2024
DOI: 10.1073/pnas.2304470121
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized BMP signaling dynamics underlie the development and evolution of digit segmentation patterns in birds and mammals

Emmanuelle Grall,
Christian Feregrino,
Sabrina Fischer
et al.

Abstract: Repeating patterns of synovial joints are a highly conserved feature of articulated digits, with variations in joint number and location resulting in diverse digit morphologies and limb functions across the tetrapod clade. During the development of the amniote limb, joints form iteratively within the growing digit ray, as a population of distal progenitors alternately specifies joint and phalanx cell fates to segment the digit into distinct elements. While numerous molecular pathways have been implicated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Firstly, models using two separate Turing patterning systems, one which defines dots, and one stripes, were shown in silico to be capable of explaining joint number, position, and orientation across various vertebrate species. Secondly, a recent paper [ 84 ] combining experimental data and in silico modelling suggested that a BMP-based Turing system may be behind these patterning events.…”
Section: Limbsmentioning
confidence: 99%
“…Firstly, models using two separate Turing patterning systems, one which defines dots, and one stripes, were shown in silico to be capable of explaining joint number, position, and orientation across various vertebrate species. Secondly, a recent paper [ 84 ] combining experimental data and in silico modelling suggested that a BMP-based Turing system may be behind these patterning events.…”
Section: Limbsmentioning
confidence: 99%
“…28-30 The activity of the PFR regulates the number and length of phalanges formed, which is the main morphological feature of digit identities in addition to their AP positions. 29,31 Currently there is a significant knowledge gap in understanding how the early and direct specification of posterior digits by SHH 3 is linked to establishment of the definitive digit pattern and identities during autopod development. This early specification must trigger molecular changes in target limb bud mesenchymal progenitor (LMP) cells that are propagated during progression of limb bud outgrowth and autopod development.…”
Section: Introductionmentioning
confidence: 99%